Analysis of Information Systems as a Tool for Enhancing Access to Justice for Marginalized Communities - Firdaus; Wahyuni, Ritna (International Journal of Integrative Sciences, 2024)
This research explores how information systems can improve access to justice for marginalized groups, focusing on the challenges they encounter within legal frameworks. Employing a mixed-methods approach, data were gathered through surveys and interviews involving both community members and legal professionals. The analysis reveals that existing information systems can enhance awareness of legal rights and streamline access to legal services. Results show that by making information systems more user-friendly, understanding and navigation of legal processes for marginalized populations can be significantly improved. The study concludes that optimizing these systems is essential for filling gaps in legal access, highlighting the importance of collaboration between legal experts and technology developers to create effective solutions that address the specific needs of these communities. This research adds to the discourse on how technology can help close the justice gap and foster a more equitable legal system